A history of early childhood education in Canada, Australia, and New Zealand - Prochner, Laurence Wayne, 1956- (UBC Press, 2009)
In the early nineteenth century, governments introduced kindergartens and infant schools to give children a head start in life. These programs hinged on new visions of childhood that originated in England and Europe, but what happened when they were exported to the colonies? This book unwinds the tangled threads of this history, from early infant schools in England to three Commonwealth countries -- Canada, Australia, and New Zealand -- where systems of educating young children were transplanted but adapted to suit local ideas, politics, and populations. This unique, comparative approach to the history of early childhood education provides fresh insight into how to reconcile educational theory and practice in an increasingly global world.